2021
DOI: 10.3390/children8020080
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Association between YKL-40, a Marker of Structural Lung Disease, and Short Telomere Length in 10-Year-Old Children with Bronchopulmonary Dysplasia

Abstract: Extremely preterm infants are born with immature lungs and are exposed to an inflammatory environment as a result of oxidative stress. This may lead to airway remodeling, cellular aging and the development of bronchopulmonary dysplasia (BPD). Reliable markers that predict the long-term consequences of BPD in infancy are still lacking. We analyzed two biomarkers of cellular aging and lung function, telomere length and YKL-40, respectively, at 10 years of age in children born preterm with a history of BPD (n = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Plasma levels of acutephase proteins such as C-reactive protein (CRP) and serum amyloid A (SAA) and of other indicators of inflammation such as TNF-α and IL-6 have also been associated with shorter LTL [8,10]. Moreover, chitinase 3-like protein levels were found to correlate negatively with spleen TL in mice (r = −0.636) [11] and with LTL in humans (r = −0.547) [12]. Chitinase enzyme activity in blood plasma is a biomarker of human aging and is elevated in agingassociated and inflammatory diseases [13].…”
Section: Telomere Biologymentioning
confidence: 99%
“…Plasma levels of acutephase proteins such as C-reactive protein (CRP) and serum amyloid A (SAA) and of other indicators of inflammation such as TNF-α and IL-6 have also been associated with shorter LTL [8,10]. Moreover, chitinase 3-like protein levels were found to correlate negatively with spleen TL in mice (r = −0.636) [11] and with LTL in humans (r = −0.547) [12]. Chitinase enzyme activity in blood plasma is a biomarker of human aging and is elevated in agingassociated and inflammatory diseases [13].…”
Section: Telomere Biologymentioning
confidence: 99%
“…Similarly, a group of researchers from Egypt [41] concluded that the diagnostic value of urine YKL-40 was higher than that of urine neutrophil gelatinaseassociated lipocalin (NGAL), proposing that it could be a valuable biomarker for the diagnosis of a UTI in febrile pediatric patients. More recently, Henckel et al [42], in a cross-sectional study that included 29 10-year-old children who had been born preterm and were diagnosed with bronchopulmonary dysplasia, nominated YKL-40 as being a novel biomarker of altered lung development due to early-life inflammation in children with a history of prematurity. Furthermore, in children with juvenile idiopathic arthritis, YKL-40 was proposed as a marker of the efficacy of biologic treatment [43], whereas in children with human immunodeficiency virus (HIV) infection, YKL-40 levels were associated with viral load and poor virologic control, as well as immune dysregulation and microbial translocation [44].…”
Section: Discussionmentioning
confidence: 99%
“…82 Additional proposed mechanisms underpinning active disease in survivors born preterm include altered immune programming, microbiome dysbiosis, epithelial abnormalities, accelerated cellular ageing, and host genetics. [82][83][84][85][86][87][88] External exposures, including tobacco smoke, air pollution and repeated viral respiratory infections, may similarly initiate cellular injury and remodelling, resulting in worsening of existing lung disease. [89][90][91] Limited data exist to draw firm conclusions about underlying mechanisms associated with PLD; although it is clear that numerous active pathways and pathologies are implicated (see Figure 2 for summary).…”
Section: "Other" Lung Function Tests To Understand Prematurity-associ...mentioning
confidence: 99%